2008
DOI: 10.1007/s10350-008-9386-1
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Track Surgery May Reduce Complications Following Major Colonic Surgery

Abstract: Fast-track is a safe and effective approach for reducing hospital stay and morbidity following major colonic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 39 publications
3
51
0
5
Order By: Relevance
“…Moreover, ERAS has provided better control of postoperative pain, faster rehabilitation, and return of gut function. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We confirmed these findings in our previous study concerning colorectal surgery in general. 18 Rectal surgery is associated with higher complication rates and longer hospital stays than is colonic surgery.…”
supporting
confidence: 81%
“…Moreover, ERAS has provided better control of postoperative pain, faster rehabilitation, and return of gut function. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We confirmed these findings in our previous study concerning colorectal surgery in general. 18 Rectal surgery is associated with higher complication rates and longer hospital stays than is colonic surgery.…”
supporting
confidence: 81%
“…van Dam et al [8] found differences in open hepatic surgery of 161 patients after a FT program (6 d vs 8 d, P < 0.0001). In colon surgery the reduction of the stay is clearly proved in several studies [6,7,18] , up to 3-4 d. Differences between our FT program and classical clinical pathway for patients who undergo laparoscopic liver surgery begin preoperatively. Due to the special characteristics of liver surgery, the possibility of being discharged less than 3 d after surgical procedure may be inconceivable.…”
Section: Dicussionmentioning
confidence: 99%
“…We did not observe a significant difference between the two groups in terms of any specific or overall complications. Around the world, larger studies have actually shown a reduction in complications in FTS groups [23]. The small sample size and non-prospective nature of this study may have been one reason why we did not make similar observations.…”
Section: Discussionmentioning
confidence: 54%